2001
DOI: 10.1023/a:1011286818733
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of our study was to assess the ability of calcium phosphate powders to serve as growth factor carriers. Vascular endothelial growth factor (VEGF), in particular, is locally involved in the bone formation process throughout osteoblast differentiation. Two different apatitic substrates were tested: hydroxyapatite (HA), widely used as biomaterial, and nanocrystalline carbonated apatite (CA), which has a composition similar to bone mineral crystals. These materials have been compared for their VEGF adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…They can only be displaced by mineral ions and/or soluble proteins with a stronger affinity for apatite surfaces but in a predicable manner, or by cell activity. This characteristic has been observed for various growth factors such as BMP-2 or VEGF [122,134], antiosteoporisis agents [135,136], and anticancer drugs such as MTX and cisplatin [124,137]. It has been reported that slow release of MTX from calcium phosphate is due to the porosity like in most of the cases but mainly due to the adsorption of MTX [137].…”
Section: Adsorption and Release Of Drugsmentioning
confidence: 88%
See 1 more Smart Citation
“…They can only be displaced by mineral ions and/or soluble proteins with a stronger affinity for apatite surfaces but in a predicable manner, or by cell activity. This characteristic has been observed for various growth factors such as BMP-2 or VEGF [122,134], antiosteoporisis agents [135,136], and anticancer drugs such as MTX and cisplatin [124,137]. It has been reported that slow release of MTX from calcium phosphate is due to the porosity like in most of the cases but mainly due to the adsorption of MTX [137].…”
Section: Adsorption and Release Of Drugsmentioning
confidence: 88%
“…Zoledronate grafted to HA coating on titanium implants shows a dose-dependent effect on the inhibition of resorption activity according to the amount of zoledronate loaded [133]. Local and slow administration of antineoplasic drugs such as methotrexate (MTX) is also useful to avoid systemic side effects and because its time effect (the sensitivity of cells to this drug increases with time) is greater than the dose effect [134].…”
Section: Adsorption and Release Of Drugsmentioning
confidence: 99%
“…Zoledronate grafted to apatite coating on titanium implants shows a dose-dependent effect on the inhibition of resorption activity according to the amount of zoledronate loaded [84]. Local and slow administration of the antineoplastic drug methotrexate (MTX) is also useful to avoid systemic side effects, and because its time effect (the sensitivity of cells to this drug increases with time) is greater than dose effect [85]. Adsorption, by contrast, leads to stable association and control of the amount of bioactive molecules contained in the solid implant, and thus of the dose released.…”
Section: Nanocrystalline Apatites As Bone Substitutes and Drug Delivementioning
confidence: 99%
“…They can only be displaced by mineral ions and/or soluble proteins with a stronger affinity for apatite surfaces but in a predictable manner, or by cell activity [86]. This characteristic has been observed for various growth factors like bone morphogenetic protein (BMP-2) or vascular endothelial growth factor (VEGF) [79,85], antiosteoporosis agents [87,88] and anticancer drugs as methotrexate and cisplatin [81,89]. It has been reported that slow release of MTX from calcium phosphate is not only due to the porosity of the inorganic matrix but mainly to the adsorption of MTX [81].…”
Section: Nanocrystalline Apatites As Bone Substitutes and Drug Delivementioning
confidence: 99%
“…Carriers fabricated from apatite materials that enable the controlled release of functional molecules are currently under investigation. Molecular release from apatite materials, initially incorporating the functional molecule, is achieved in vivo by desorption, depending on the local environment [87][88][89][90]. Therefore, an understanding of the adsorption and desorption kinetics of the functional molecules of HAp is crucial for achieving optimal drug release.…”
Section: Apatite Materials As Drug and Gene Deliv-ery Systemsmentioning
confidence: 99%